Witch(craft) Subversion in Live Events (Performance Art) in Croatia: From Art to Everyday Praxis - MARJANIĆ, Suzana (Studia Universitatis Babeș-Bolyai Dramatica, 2020)
This paper offers an interpretative review of artists on the Croatian scene who use in their actions and performances the strategy of ‘witchcraft performance’ as matrix of subversion of the existing model of ‘desirable appearance’, as performative deviation from the desirable image of womanhood, but also as a kind of decision to express protest and subversion. Some women artists, like Neda Šimić-Božinović and Xena L. Županić, alongside the performance of witchcraft subversion, are also united by the voco-performance with which they approximate animal vocalisation as the source of logos.